Retrospective Review of Surgery for Urogynaecological Prolapse and Stress Urinary Incontinence using Tape or Mesh : Experimental Statistics, Northern Ireland, April 2008 - March 2017.: Experimental Statistics, Northern Ireland, April 2008 - March 2017. (2018) - Northern Ireland., Department of Health., Information and Analysis Directorate,
No abstract available